2019
DOI: 10.3390/en12122401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Concentration on Tracking Resistance of ATH-Filled Silicone Rubber Nanocomposites

Abstract: It is necessary for polymeric materials to have superior tracking resistance against various stress conditions for outdoor applications. In this study, the effect of nano-sized alumina tri-hydrate (ATH) particles on the tracking resistance of silicone rubber (SiR) is studied. Specimens with filler loadings of 1, 3, 5, 10, and 20 wt % are used for performance characterization. From the inclined plane test (IPT) results, apparent improvement in tracking resistance was achieved by mixing 3 wt % of nano-sized fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Insulation materials are subjected to mechanical, electrical and environmental stresses [25], as well as electrostatic discharges, which may generate cracks in wiring insulation materials [26]. In particular, environmental stresses such as ultraviolet radiation from sunlight, moisture, contaminants and pollution such as ozone or acid rain [27] and aged polymeric insulation materials [28] could degrade the material due to surface tracking [29] and erosion [30]. Wire insulation materials present different unanticipated failure modes, such as arc tracking, arcing and finally insulation flashover in order of increasing severity [31].…”
Section: Factors Affecting Arc Trackingmentioning
confidence: 99%
“…Insulation materials are subjected to mechanical, electrical and environmental stresses [25], as well as electrostatic discharges, which may generate cracks in wiring insulation materials [26]. In particular, environmental stresses such as ultraviolet radiation from sunlight, moisture, contaminants and pollution such as ozone or acid rain [27] and aged polymeric insulation materials [28] could degrade the material due to surface tracking [29] and erosion [30]. Wire insulation materials present different unanticipated failure modes, such as arc tracking, arcing and finally insulation flashover in order of increasing severity [31].…”
Section: Factors Affecting Arc Trackingmentioning
confidence: 99%
“…This could be due to the effect of the addition of nanofillers. It is reported in recent literature that the addition of a small amount of nanofiller improves the tracking resistance of polymeric insulations [25][26][27][28].…”
Section: Analysis Of Leakage Current Variations During Trackingmentioning
confidence: 99%
“…Khan, H. et al investigated the effect of ATH-SiO 2 reinforced RTV silicone rubbers in improving the tracking and erosion resistance along with water absorption resistance properties [25,26]. Jeon, Y. et al studied the effect of different filler concentration on RTV silicone rubber on improving the tracking resistance, and they found that the tracking performance is similar to 20% by weight SiO 2 /SiR micro composites can be achieved with 5% by weight ATH/SiR nanocomposites [27].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the tracking resistance of a polymeric insulation material, hydrophobicity of the polymer surface should be modified and aluminum trihydroxide (ATH) particles are incorporated into the insulating material. [15][16][17] When the former condition is satisfied, moisture penetration is prevented due to the water repellency of the surface and the local distortion of electric field is prevented by suppressing the accumulation of contaminants, thereby improving tracking resistance. In the latter condition, ATH particles generate water molecules and absorb reaction heat with an endothermic process of 1.17 kJ/g during the decomposition at about 220 C. The generated water molecules also absorb evaporation heat during the volatilization.…”
Section: Introductionmentioning
confidence: 99%